Pitying the Desolation of Such a Place: Rebuilding Religious Houses and Constructing Memory in Aquitaine in the Wake of the Viking Incursions - Jones, Anna Trumbore (Viator, 2006)
Abstract This article examines the consequences of the ninth-century Viking incursions for religious houses in the southwest of France, and the portrayal of those raids in contemporary and later medieval sources. Focusing on three houses in particular—Saint-Hilaire and Saint-Maixent in the Poitou and Saint-Cybard in Angoulême—the author uses both narrative and diplomatic evidence to make two arguments. First, the charter record of these houses indicates that although the Viking raids did cause damage, which was often exacerbated by opportunistic predation by locals, recovery took place relatively quickly. Second, the accounts in tenth-century and later medieval texts, in contrast to the contemporary charter evidence, often evoke more persistent destruction at these houses. This disjunction occurred because the authors of those later accounts shaped their portrayals of the Vikings and the consequences of the raids to serve purposes such as glorifying a restorer or emphasizing a reform in observance.